Case Based Learning (CBL) dalam Pembelajaran IPA: Suatu Kajian Literatur 2014-2023 - Medila, Gita; afrahamiryano, afrahamiryano; Wati, Darmanella Dian Eka; Gazali, Fauzana (Pendidikan Biologi FKIP UMMY, 2024)
This literature study research aims to determine the use of CBL in Science Education. The method used in writing this journal is a literature review beginning with determining the topic, namely Case Based Learning in Science Education, then determining keywords to search for the journal, the keywords used include: Case Based Learning, Case Method in Science Education, Journal search is limited year from 2014-2023. Journal consists of national and international journals, in English and Indonesian. The result obtained by the CBL learning model can improve student learning achievements. Achievements that have increased include critical thinking skills, analytical thinking, problem-solving, and cognitive abilities. The development of learning media in the form of CBL-Based modules, Vidio, e-Book, Flipbook, and books also has good practical value and validity.